Клініко-лабораторні особливості первинного гіпотиреозу в поєднанні з артеріальною гіпертензією - Зелінська, Н. Б.; Ларін, О. С.; Паньків, В. І.; Гирявенко, О. Я. (Clinical Endocrinology and Endocrine Surgery, 2010)
Article deals with data about significant differences in a coarse of arterial hypertension (AH) depending on functional thyroid gland state. Proved increase in frequancy of hypertonic crisis development and insufficiency of blood circulation and quantity of blood aterogenic fractions were observed in hypothyroidism. Among dominated violence of heart rhythm in patients with hypothyroidism is supraventricular extrasystolia, concentric hypertrophy of left ventricle is offen registrated. Hypothyroidism compensation favours of prooved improvement of structural and functional heart characteristics and parameters of lipid profile.